Osteoporosis in axial radiographic spondyloarthritis: diagnostic limitations of bone mineral density and the need for comprehensive fracture risk assessment - Paweł Żuchowski; Marta Dura; Daniel Jeka; Rafał Wojciechowski; Maciej Bierwagen; Michał Kułakowski (Rheumatology)
Axial radiographic spondyloarthritis (r-axSpA) is a chronic inflammatory joint disease that leads to a considerable decline in the quality of life of patients by impairment of function and mobility, which, in turn, brings about a deterioration of both physical and mental health. Osteoporosis (OP) is a significant issue in the course of r-axSpA. Fractures resulting from OP complicate the treatment of the underlying disease and reduce the quality of life of patients. The aim of this paper is to discuss currently available diagnostic methods for OP and highlight why the gold standard for diagnosis – the assessment of bone mineral density via dual-energy X-ray absorptiometry – is not sufficient for patients with r-axSpA.